Nrf2 Regulates Neurogenesis and Protects Neural Progenitor Cells Against Aβ Toxicity. (July 2014) - Kärkkäinen, Virve; Pomeshchik, Yuriy; Savchenko, Ekaterina; Dhungana, Hiramani; Kurronen, Antti; Lehtonen, Sarka; Naumenko, Nikolay; Tavi, Pasi; Levonen, Anna‐Liisa; Yamamoto, Masayuki; Malm, Tarja; Magga, Johanna; et al.
Abstract Neural stem/progenitor cells (NPCs) proliferate and produce new neurons in neurogenic areas throughout the lifetime. While these cells represent potential therapeutic treatment of neurodegenerative diseases, regulation of neurogenesis is not completely understood. We show that deficiency of nuclear factor erythroid 2‐related factor (Nrf2), a transcription factor induced in response to oxidative stress, prevents the ischemia‐induced increase in newborn neurons in the subgranular zone of the dentate gyrus. Consistent with this finding, the growth of NPC neurospheres was increased by lentivirus‐mediated overexpression of Nrf2 gene or by treatment with pyrrolidine dithiocarbamate (PDTC), an Nrf2 activating compound. Also, neuronal differentiation of NPCs was increased by Nrf2 overexpression or PDTC treatment but reduced by Nrf2 deficiency. To investigate the impact of Nrf2 on NPCs in Alzheimer's disease (AD), we treated NPCs with amyloid beta (Aβ), a toxic peptide associated with neurodegeneration and cognitive abnormalities in AD. We found that Aβ1–42‐induced toxicity and reduction in neurosphere proliferation were prevented by Nrf2 overexpression, while Nrf2 deficiency enhanced the Aβ1–42‐induced reduction of neuronal differentiation. On the other hand, Aβ1–40 had no effect on neurosphere proliferation in wt NPCs but increased the proliferation of Nrf2 overexpressing neurospheres and reduced it in Nrf2‐deficient neurospheres. These results suggest that Nrf2 is essential for neuronal differentiation of NPCs, regulates injury‐induced neurogenesis and provides protection against Aβ‐induced NPC toxicity. Stem Cells2014;32:1904–1916